The correlation of the forkhead transcription factor foxo1 expression and histopathological pancreatic lesions in dogs - Firas M. Abed; Ahmed N. Abduljawaad; Omar A. Al-Mahmood; Karam H. Yehia; Hana Kh. Ismail (Iraqi Journal of Veterinary Sciences)
The objective of the current research was to characterize the correlation of Forkhead transcription factor and histopathologic findings of dogs’ pancreatic lesions. The study revealed a negative linear correlation (Correlation Coefficient 0.96) between lesions frequences and FOXO1 (lesions frequences move in opposing directions). Lesion frequences reduce as FOXO1 rises. Samples collected from the necropsy unit of veterinary teaching hospital at University of Mosul, college of veterinary medicine, to determine and confirm any histopathologic evidence of specific lesions these specimens histologically examined. In dogs, pancreatic lesions can range from mild inflammation (pancreatitis) to more severe conditions such as pancreatic cancer. Focusing on histopathological changes can help identify the correlation with FOXO1 expression. Various types of lesions were observed in the 17 pancreatic samples from dogs; however, none have been showed any evidence of neoplasia. Despite a lack of gross lesions, 14 samples (82.35%) exhibited microscopic pathological changes. Three samples (17.64%) revealed normal histology. In total, 12 types of microscopic lesions were identified. Among the 14 samples, degenerative changes, congestion, edema, coagulative and fat necrosis, as well as inflammation were detected in some samples. Multiple lesions, including fibrosis, hyperplasia, and atrophy, were observed in other samples. Additionally, cyst formations, metaplasia, and granulation tissue were determined. Dogs were randomly chosen, and all pancreatic samples were assessed through histopathological and immunohistochemical evaluation. This study concludes that lesions frequences move in opposing directions. Lesion frequences increase as FOX01 descend.